Genome-wide sequencing identified extrachromosomal circular DNA as a transcription factor-binding motif of the senescence genes that govern replicative senescence in human mesenchymal stem cells - Yang, Wei; Ji, Wei; Liao, Boyu; Li, Zhongbo; Wang, Jian; Lin, Haishu; Wang, Jingbo; He, Qian (Frontiers in Cellular Neuroscience, 2024)
Mesenchymal stem cells (MSCs) have long been postulated as an important source cell in regenerative medicine. During subculture expansion, mesenchymal stem cell (MSC) senescence diminishes their multi-differentiation capabilities, leading to a loss of therapeutic potential. Up to date, the extrachromosomal circular DNAs (eccDNAs) have been demonstrated to be involved in senescence but the roles of eccDNAs during MSC senescence are yet unknown. Here we explored eccDNA profiles in human bone marrow MSCs (BM-MSCs), and gene annotation analysis revealed that the majority of eccDNA were mapped in the intron regions with limited BM-MSC enhancer overlaps.Sequentially, we discovered that these eccDNA motifs in senescent BMSCs acted as motifs for binding transcription factors (TFs) of senescence-related genes. These findings are highly significant for identifying biomarkers of senescence and therapeutic targets in mesenchymal stem cells (MSCs) for future clinical applications. The potential of eccDNA as a stable therapeutic target for senescence-related disorders warrants further investigation, particularly exploring chemically synthesized eccDNAs as transcription factor regulatory elements to reverse cellular senescence.